2001
DOI: 10.1046/j.1365-2672.2001.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria from healthy oral cavity of Thai volunteers: inhibition of oral pathogens

Abstract: The aims of the present study were to screen and characterize the antimicrobial lactic acid bacteria which were isolated from healthy oral cavities of Thai volunteers, and to characterize their inhibiting substances. Among 3790 isolates (suspected to be lactic acid bacteria) from 130 volunteers, ®ve showed an appreciable effect against Sarcina lutea ATCC 9341, Bacillus cereus ATCC 11778, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Streptococcus mutans DTMU 1, Strep. salivarius DTMU 1, Strep. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 20 publications
4
114
0
3
Order By: Relevance
“…Sookkhee et al [25] recently found that the anticandidal activity of some oral Lactobacillus strains was not inhibited by heat treatment, which also suggested alternative mechanisms of inhibition. In fact, several antifungal substances such as cyclic dipeptides, pyroglutamic acid and other substances of low molecular mass, such as lactones, produced by different Lactobacillus species, have recently been characterized [19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Sookkhee et al [25] recently found that the anticandidal activity of some oral Lactobacillus strains was not inhibited by heat treatment, which also suggested alternative mechanisms of inhibition. In fact, several antifungal substances such as cyclic dipeptides, pyroglutamic acid and other substances of low molecular mass, such as lactones, produced by different Lactobacillus species, have recently been characterized [19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during the past few years, several investigators have reported the use of probiotics for the maintenance of oral health [12,16]. Some studies have confirmed that lactobacilli can inhibit the growth of periodontopathogens, including P. gingivalis, Prevotella intermedia, and Aggregatibacter actinomycetemcomitans [17,18]. In our previous study, we have also reported the inhibitory effect of Lactobacillus acidophilus on the growth of P. gingivalis [19].…”
Section: Introductionmentioning
confidence: 86%
“…Lactobacillus paracasei constitutes a substantial part of the Lactobacillus flora of the human intestinal mucosa (Ahrne et al 1998). Studies have shown that certain strains of L. paracasei can produce anti-bacteria and anti-yeast compounds in the human vagina and oral cavity (Ocaña et al 1999;Sookkhee et al 2001;Atanassova et al 2003). In addition, the strain has played a general beneficial health role as a probiotic, and the important traits of this species include antihypertensive, antiinflammatory, diuretic, sedative, and anti-diabetic (Adeghate and Ponery 2002;Jahreis et al 2002;Wang et al 2004;Komatsuzaki et al 2005).…”
Section: Introductionmentioning
confidence: 99%